Relación Entre Los Deberes Para Casa y el Rendimiento Académico del Alumnado de Primaria - Mª Elena Parra González; Christian A. Sánchez Núñez (European Scientific Journal, ESJ, 2018)
Homework is a complex phenomenon that is related to many variables to consider. Many authors defend the relationship of homework with the improvement of the students’ academic performance. This descriptive and correlational research studies and analyses variables, which may have a significant influence between homework and academic performance. The study sample was composed of 747 students, 679 families, and 57 teachers of 4th, 5th, and 6th grade of Primary Education. The informants answered three questionnaires built ad hoc for each group. Among the main variables and relationships analyzed, the frequency of the performance of homework, doing homework with help, the time invested in them or the degree of difficulty of homework, which were all related to performance, were found. Prior to the main conclusions of the study, it was found that there is no significant relationship between investing more time on homework and getting better grades; there is a relationship between perceived difficulty in tasks and poor performance; students have better grades when they try harder, have optimal conditions for doing homework and when the type of homework entails studying and/or reviewing.